Determination of Harvesting Time and Fermentation Conditions of Coffee (Coffee sp) Beans Based on the Fruit Pericarp Enzyme Activity) - Muhammad Said Didu (Jurnal Teknologi dan Industri Pangan, 2001)
Pectinase enzyme of coffee pericarp, containing pectinesterase and polymetilesterase, is potential to determine harvesting time or to classify coffee beans. The activity of the enzyme on the green fruit is higher than on the yellow one. When the fruit become light red, the activity increaed for the second time and then decrease when the fruit is overripe (dark colored)The optimum fermentation condition of the fruit is depending on the maturation degree. Study on the fermentation process at 25oC, suggest sorting of harvesting fruits in three groups. (1) fruits are harvested 9-24 days after the fruits reach its yellowish green color, Ao, (2) 25 - 32 days after Ao, and (3) 33 - 38 days after Ao. Fermenting at 35o C grouping into four types of maturation degree. (1) 9 - 11 days after Ao, (2) 12 - 22 days after Ao, (3) 23 - 30 days after Ao, and (4) 24-36 days after Ao. The optimum harvesting time is when the beans reach light red until the color starts getting dark. The optimum activity of the enzyme pectinase is at 35oC.